SOCIOETHNIC GROUPS OF LATGALE IN 16-18th CENTURIES ACCORDING TO RĒZEKNE DISTRICT INVENTORY AND SOUL AUDIT DATA - Dzenis, Agris (Via Latgalica, 2017)
One of the most sustainable constituents of Latgalian culture is historically socioethnic groups. A socioethnic group is a community of residents determined by specific ethnic and historical circumstances and a more or less fixed place in social hierarchy. Until now, few studies have used the written sources dated 1599, 1712, 1738 and 1765 the Rzecpospolita estate Rzezyca (Rēzekne) district country manor inventory, written in Polish, stating the names of the hosts of peasants’ houses which reflects the dynamics of socioethnic group formation. Souls audit legislation written in autumn 1772 in Russian is the oldest source of information related to the relatively wide range of kinds of Latgale population concerning age, place of residence and kinship ties. The inventory by parishes and villages included host names, which made it possible to create an inventory of the names of Latvians living in Latgale, Jewish names, people with Slavic and Old Believers’ specific names, which made it possible to determine the trends of population and ethnic composition. Following a long period of war and political chaos in 1599 Rēzekne district inventory list of seven parishes recorded only 104 farms. The foreign ethnic group indicates the presence of certain non-Latvian peasant family names – Litvil, Hanekenon, Gadpian, which in subsequent documents do not occur. The document recorded seven Latgalian Latvian names of specific locations referred to in later centuries – for example, Kemp in Makašāni (Makaszany) parish, Laizan, Greidan, Stylba, and Spungian. The 1712 inventory recorded 232 village farms. This number after the Great Northern War and pest is considered as relatively high. In the same year, in Krīvāni (Kryvan), Rāzna (Razien) and Osyune (Osyn) parish were listed individuals with Polish surnames – Dukalski, Borkevicz, Lipski, Harasimowicz. For the first time there are some Jewish names listed. 1738 for Latgale is a peaceful and politically stable period. The number of farms has increased to 291. Among these, 34 farms in Krīvāni, Lobuordi (Loborsky), Rāzna and Osyune parishes were inhabited by Poles. Most of them were public service people – the so-called bojary or personally free landowners. There were mentioned only two hosts called moskal – strangers from Russia. It should be noted that in 1712 and 1738 inventories there were mentioned some Latvian landowner families in Nautrani parish: Laizan, Rudborz, and Jurdz. The biggest number of Russian Old Believers was in 1765. In that year, 119 villages with an average of five farms within each already recorded 20 villages inhabited by Russians and Poles. In addition, there were 10 Russian and Latvian mixed populated villages and eight villages populated by Latvians and Poles. Year 1772 souls audit shows that many of the Old Believers have not come from Russia, but from Rzecpospolita territory, modern time Belarus. Souls audit provides information on the crown and 42 private manors. For the first time both sexes and all nationalities are represented in the audit. This source provides a very good opportunity to study the ethnic composition, age and kinship with mathematical methods. Most of the farmers were Latvians. The second largest ethnic group of farmers was Russian Old Believers, the third – the Belarussians. The Russians, the Poles and Latvians inhabited villages and free villages – sloboda. Socially most diverse ethnic group was Poles, among which there were large and small landlords, village residents, farmers, and manor servants. In 34 estates Jews were listed – a socially homogenous and well-organized group. All Jews in Rēzekne district belonged to the Kahal in Kruoslova (Kreslaw), which was a Jewish self-government body with judicial functions. In 3 manors were mentioned Gypsies engaged in agriculture. Social groups in Rēzekne district consisted of three religious and spatially demarcated ethnic groups: Latvians, Russian Old Believers, and Belarussians. All ethnic groups of farmers in year 1772 lived in big families in which three generations lived together – parents, unmarried children and several married children, grandchildren and foster children. The servants mostly were close relatives. Latvian villages were mostly inhabited by one family and the names of these villages were derived from the surname of that family. From 1772 souls audit data it can be inferred that every ethnic group was a closed living space. Latvians, Russians and Belarusians lived in villages and sloboda, Poles – in manors and sloboda, Jews – in manors. Up to the 20th century the living space was maintained as a cultural space. Ethnic group-specific traditions were passed on to future generations. Belonging of a social group to a distinct ethnicity was not a strict criterion. Diversity of ethnic groups is most prominently seen in farmers’ social group.